Interpreting Surah Al-Anfal Verse 26 through Hasan Hanafi’s Critical-Emancipatory Hermeneutics: Reinterpreting Revelation for Social Justice - Azizah, Khoridatul; Hidayati, Tri Wahyu (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2025)
In the face of growing social inequalities and marginalization in the modern Muslim world, Qur’anic interpretation is increasingly called upon to address real-world injustices. Surah Al-Anfal verse 26 highlights the early Muslims' experience of oppression, fear, and poverty, followed by divine empowerment. This verse offers a theological entry point for rethinking the Qur’an’s role in social transformation. This study aims to reinterpret Al-Anfal:26 through the lens of Hasan Hanafi’s critical-emancipatory hermeneutics, which views revelation not merely as normative doctrine but as a call to action for liberation and justice. The research adopts Hanafi’s three-stage hermeneutical method: (1) historical awareness—understanding the socio-political context of the verse; (2) eidetic analysis—extracting its essential ethical meaning; and (3) practical engagement—applying its message to contemporary struggles. The findings show that when interpreted through this gacor777 framework, the verse becomes a powerful call for solidarity with the oppressed and for active resistance against systemic injustice. It encourages Muslims to see the Qur'an as a living, historical text that responds to human suffering with moral urgency. This study concludes that Surah Al-Anfal:26 provides not only historical insight but also a theological foundation for Islamic liberation theology. The research contributes to contemporary Qur’anic studies by demonstrating how contextual hermeneutics can make sacred texts more responsive to the ethical and political demands of the present.